Cognitive Level of Essay Questions in the Islamic Religious Education Textbook for Class XI - Toyibah, Siti (Centre for Literary and Cultural Studies, 2025)
This study aims to analyze the cognitive level of essay questions in the Islamic Religious Education textbook for Class XI. The background of this research highlights the importance of higher-order thinking skills (HOTS) in 21st-century education, which necessitates evaluation questions capable of measuring students' analytical and critical skills. This research adopts a qualitative approach using the content analysis method. The method involves categorizing questions based on the revised Bloom's Taxonomy, which includes cognitive levels from C1 to C6. The analysis results show that out of 50 essay questions analyzed, 44% are at the C1 level, 38% at the C2 level, 12% at the C3 level, 4% at the C5 level, and 2% at the C6 level, with no questions at the C4 level. The conclusion of this study is that the majority of questions remain at the basic cognitive level, emphasizing basic recall and understanding. The implication of these findings is the need to improve the quality of questions to better encourage students' critical and analytical thinking skills comprehensively.